C3N4-sensitized TiO2 nanotube arrays with enhanced visible-light photoelectrochemical performance1. Issue 27 (21st July 2015) - Yang, Manman; Liu, Juan; Zhang, Xing; Qiao, Shi; Huang, Hui; Liu, Yang; Kang, Zhenhui
<x xml:space="preserve">Abstract</x> A C3N4-sensitized TiO2 nanotube array-based photoanode was designed and fabricated via the in situ growth of C3N4 on the surface of TiO2 nanotube, which shows stable and significantly improved PEC activity for the hydrogen generation under visible light irradiation.